Diagnostic and Therapeutic Neuroradiology A Case-Based Guide to Good Practice (Springer International Publishing, 2018)
This book presents a wide-ranging series of illustrative clinical cases that cover the main pathologies and areas of interest in diagnostic and therapeutic neuroradiology. The aim is to enable the reader to learn important lessons from real cases that exemplify the caseload and capabilities of a large, modern neuroradiology department. The cases are presented in a quiz format. For each one, the first page documents clinical and imaging findings, followed by questions concerning these findings, differential diagnosis, and other aspects. On the second page, the answers are provided, with concise explanation and discussion. Attention is also drawn to the relevant available literature. Most of the cases derive from the Department of Neuroradiology at the University Hospital Center of Porto (Portugal), which is staffed by a large multidisciplinary team providing cutting-edge services. In addition, some cases from other centers have been included to ensure wider representation of experience. The book will be of particular value for residents and fellows in neuroradiology, radiology, neurology, and neurosurgery.